The impact of platelet indices on ischemic stroke: a Mendelian randomization study and mediation analysis - Li, Yang; Xiang, Wenping; Xue, Hui; Meng, Tianyu; Zhang, Tianyou; Zhang, Jinfeng; Wang, Jingbo; Zhao, Jili; Wang, Baojun (Frontiers in Neurology, 2023)
Introduction Platelet indices (PIs) are hematological parameters that indicate the number, morphology, and activation of platelets. Although some clinical trials suggest an association between PIs and the risk of stroke, the lack of robust evidence is attributed to confounding effects and reverse causation. Objective This study aimed to evaluate the association between PIs and stroke risk through Mendelian randomization (MR) while exploring the mediating effect of blood pressure in this association. Methods We identified genetic variants associated with PIs, including platelet count (PLT), platelet distribution width (PDW), mean platelet volume (MPV), and platelet crit (PCT), in the UK Biobank (n = 350,474). Relevant genome-wide association studies were utilized to gather summary statistics pertaining to the traits of interest. We primarily used the inverse-variance weighted analysis to obtain estimates for individual causal power. Result We observed a positive correlation between genetically predicted increases in PCT levels with the stroke onset [PCT: OR (95%CI) = 1.113(1.047, 1.183), p < 0.001]. However, no significant causal relationship was found between PLT, PDW, and MPV and the risk of stroke [PLT: OR (95%CI) = 1.037(0.979, 1.098), p = 0.221; PDW: OR (95%CI) = 0.973(0.923, 1.024), p = 0.294; MPV: OR (95%CI) = 0.990(0.945, 1.038), p = 0.675]. Multivariable MR analyses and mediation analysis found that the proportion mediated by systolic blood pressure (SBP) is 23.71% [95%CI (10.85–33.31%)] and the proportion mediated by diastolic blood pressure (DBP) is 28.09% [95%CI (12.92–39.63%)]. Conclusion This large MR study presents evidence for the potential causal relationship between the PCT level and the risk of ischemic stroke, which might be mediated by blood pressure.